IMPLEMENTASI METODE SIMA’AN Al-QUR’AN DALAM MENINGKATKAN HAFALAN SANTRI PUTRI PONDOK PESANTREN MAHASISWA AL-HIKAM MALANG - KHASANATUN, ALFA; Muhammad Syauqillah (STAI Ma'had Aly Al-Hikam Malang, 2024)
The Qur'anic sima'an method is used to maintain and strengthen the memorization of the Qur'an, so that the memorization is maintained and smooth. In sima'an activities, memorizers can mark verses that have similar sounds, making it easier for them to remember and compare. Pondok Pesantren Mahasiswa Al-Hikam Malang applies this method to help tahfidz students maintain their memorization. This study aims to describe the implementation of the sima'an Al-Qur'an method in improving the memorization of female tahfidz students in this pesantren, as well as identifying the supporting and inhibiting factors. Using a qualitative approach, this study collected data through interviews, observations, and documentation with data sources from ustadzah, administrators, and female tahfidz students. Analysis techniques include data reduction, data presentation, and conclusion drawing, and data validity is guaranteed by source triangulation. The results showed that the sima'an method was applied through ziyadah sima'an, muraja'ah, and joint sima'an activities. Supporting factors include self, parental support, ustadzah guidance, the role of administrators, strong intentions, and remembering the time of sima'an. The inhibiting factors include lack of accuracy, looking at the Mushaf when memorizing, laziness, the influence of cellphones, rushing, difficulty managing time, and mutasyabihat verses